Peran Petugas Rutan Dalam Menanggulangi Tindak Pidana Penganiayaan Di Rumah Tahanan Negara - Oswan, Jonli; Santina, Rika; Melati, Dwi Putri (Universitas Sang Bumi Ruwa Jurai, 2025)
This research aims to analyse the role of officers at the Class II B Krui State Detention Center (Rutan), Pesisir Barat, Lampung, in dealing with criminal acts of abuse between prisoners. Detention centers as institutions responsible for coaching prisoners often face problems of violence in cells which hinder the coaching process. One of the violent incidents that occurred at Krui Detention Center involved several inmates who were involved in a fight that resulted in abuse. This research focuses on how detention center officers carry out their functions in preventing and handling criminal acts of abuse, as well as the factors that influence the occurrence of violence within the institution. The research method used is a qualitative approach using interviews and observations of officers and prisoners in detention centers. It is hoped that the results of the research will provide an overview of the challenges faced by officers in creating safe and conducive conditions, as well as provide recommendations for improving more effective monitoring and coaching systems in detention centers. It is also hoped that this research can strengthen the correctional system so that prisoners can return to society with better behavioral changes.